Aquaponics and its potential aquaculture wastewater treatment and human urine treatment - Sánchez, Henrique Junior Aiveca (2014)
The main objective of this thesis is to study the developing fields of aquaponics and its potential for aquaculture wastewater treatment and human urine treatment. Aquaponics is a food production system which combines fish farming (aquaculture) with soilless crop farming (hydroponics). In this thesis the concept of aquaponics and the underlying processes are explained. Research on aquaculture wastewater and human urine wastewater is reviewed and its potential application with aquaponic systems is studied. An overview of the different types of aquaponic systems and current research on the field is also presented. A case study was conducted in a farm in Askeröd, Sweden, which involved building two aquaponic systems (System 1 and System 2) and a human urine-based aquaponic system (System 3), with different degrees of component complexity and sizes. The design, building and monitoring of System 1, System 2 and System 3 was documented and described in detail. Four day experiments were conducted which tested the evolution in concentration of Total Ammonia Nitrogen (NH4+/NH3), Nitrite (NO2-), Nitrate (NO3-), Phosphate (PO43-), and Dissolved Oxygen (O2) after an initial nutrient input. The goal was to assess the concentrations of these parameters after four days and compare them with relevant literature examples in the aquaculture industry and in source-separated urine research. Neither of the two aquaponic systems (System 1 and System 2) displayed all of the parameter concentrations in the last day of testing below reference values found in literature. The best performing of the aquaponic systems was the more complex system (System 2) combining the hydroponic Nutrient Film Technique with a Deep Water Culture component, with a Total Ammonia Nitrogen concentration of 0,20 mg/L, a Nitrite concentration of 0,05 mg/L, a Nitrate concentration of 1,00-5,00 mg/L, a Phosphate concentration of <0,02 mg/L and a Dissolved Oxygen concentration of 8,00 mg/L. The human urine-based aquaponic system (System 3) underperformed in achieving the reference concentration values in literature for most parameters. The removal percentage between the higher recorded values after the input addition and the final day of testing was calculated for two literature examples of separated urine treatment and System 3. The system had a removal percentage of 75% for Total Ammonia Nitrogen, 98% for Nitrite, 25% for Nitrate and 50% for Phosphate. These percentages still underperformed literature examples in most of the tested parameters. The results gathered allowed to conclude that while aquaculture wastewater treatment and human urine treatment is possible with aquaponics systems, overall these did not perform as well as some examples found in recirculating aquaculture systems and source-separated urine treatment literature. However, better measuring techniques, longer testing periods and more research is recommended in this field in order to draw an improved representative conclusion.